Association of serum and aqueous humor myonectin concentrations with diabetic retinopathy - Huibo Sun (Nature Portfolio, 2021)
Abstract Myonectin, a newly discovered myokine, enhances fatty acid uptake in cultured adipocytes and hepatocytes and suppresses circulating levels of free fatty acids in mice. This study is performed to evaluate the association between serum and aqueous humor myonectin concentrations with diabetic retinopathy (DR). This study was performed in a population of 228 patients with type 2 diabetes (T2DM) and 72 control subjects. Diabetic patients were then divided into T2DM patients without DR, non-proliferative diabetic retinopathy (NPDR) patients, and proliferative diabetic retinopathy (PDR) patients. Serum and aqueous humor myonectin concentrations were significantly lower in the case group than in the control group. PDR patients showed significantly decreased serum and aqueous humor myonectin concentrations than in the other two T2DM patients. In addition, NPDR patients showed significantly lower serum and aqueous humor myonectin concentrations than T2DM patients without DR. Logistic regression analysis demonstrated that serum and aqueous humor myonectin was correlated with a decreased risk of T2DM and DR. Simple linear regression analysis showed that serum myonectin was negatively correlated with duration of disease, body mass index (BMI), and HbA1c. Duration of disease and BMI were still correlated with the serum myonectin after a multiple linear regression analysis. Aqueous humor myonectin was negatively correlated with duration of disease, systolic blood pressure (SBP), and diastolic blood pressure. Duration of disease and SBP was still correlated with the aqueous humor myonectin after a multiple linear regression analysis. Our investigation indicates an inverse association of serum and aqueous humor myonectin with DR.